KEHILANGAN HASIL PEMANENAN JAGUNG MENGGUNAKAN ALAT COMBINE HARVESTER MAXXI CORN TIPE-G DI DESA LOPANA KECAMATAN AMURANG TIMUR KABUPATEN MINAHASA SELATAN - Juanly J. Mamahit; Frans Wenur; Lady C. Ch. E. Lengkey (COCOS, 2022)
AbstractThe objective of this study is to determine the harvest loss in corn using the CombineHarvester Maxxi Corn Type-G. This research was conducted in Lopana Village, East AmurangDistrict, South Minahasa Regency, North Sulawesi Province in January-July 2021. Harvestingwas conducted with the Combine Harvester Maxxi Corn Type-G on corn plants of the Pertiwivariety that were ready to harvest. This study used experimental methods. Data collection wasdone by observing directly on the corn harvested with the machine. The experiment conducted 3repetitions. The results of this study showed that the loss of spilled corn during harvestingamounted to 0.046% ±0.004%. Unharvested losses amounted to 0.363% ±0.054%. Losses due tolagging on the machine amounted to 0.965% ±0.124%. The total yield loss during the harvestingprocess using the Combine Harvester Maxxi Corn Type-G is 1.374% ±0.101%.Key words: losses, combine harvester, corn